Conditional knockdown of hepatic PCSK9 ameliorates high-fat diet-induced liver inflammation in mice - Zhang, Xue-Ying; Lu, Qing-Qing; Li, Yan-Jie; Shi, Shan-Rui; Ma, Chao-Nan; Miao, Miao; Guo, Shou-Dong (Frontiers in Pharmacology, 2025)
InstructionAccumulating evidence has shown that proprotein convertase subtilisin/kexin type 9 (PCSK9) is associated with inflammation in the vascular system. However, the roles of PCSK9 in hepatic inflammation remain unclear. Because PCSK9 is mainly expressed in the liver and modulates lipid uptake through low-density lipoprotein receptor family members, the present study aimed to elucidate the effect of conditional knockdown of hepatic PCSK9 on hyperlipidemia-induced inflammation and the underlying mechanisms of action.MethodsPCSK9flox/flox mice were bred with ALB-Cre+ mice to obtain hepatic PCSK9(−/−), PCSK9(+/−), and PCSK9(+/+) mice. These mice were fed with a high-fat diet for 9 weeks to induce inflammation. The effects of conditional knockdown of hepatic PCSK9 on inflammation and the underlying mechanisms were investigated by molecular biological techniques. Moreover, the findings were verified in vitro using HepG2 cells.Results and DiscussionConditional knockdown of hepatic PCSK9 remarkably decreased plasma levels of total cholesterol and alleviated hyperlipidemia-induced liver injury. Mechanistically, conditional knockdown of hepatic PCSK9 significantly reduced the levels of pro-inflammatory factors by downregulating the expression of Toll-like receptors, mitogen-activated protein kinase (MAPK), and phosphoinositide-3 kinase/protein kinase B, which subsequently attenuated the expression of downstream molecules, namely nuclear factor kappa-B and activator protein-1. The related mechanisms were confirmed using lipid-loaded HepG2 cells together with PCSK9 siRNA, alirocumab (anti-PCSK9 antibody), and/or a p38-MAPK inhibitor. These findings confirmed that conditional knockdown of hepatic PCSK9 attenuates liver inflammation following hyperlipidemia induction by modulating multiple signaling pathways; this suggests that targeting PCSK9 knockdown/inhibition with appropriate agents is useful not only for treating hyperlipidemia but also for ameliorating hyperlipidemia-induced liver inflammation.